Disparities in adolescent mental health-related National Health Service presentations in England: secondary school cohort study - Lewis, Kate; Dale, Helen; Lewer, Dan; Downs, Johnny; Blackburn, Ruth (International Journal of Population Data Science, 2026)
Robust national evidence on mental health-related service use is necessary to guide equitable policy interventions. We described referrals to mental health services, mental health-related emergency department attendances and hospital admissions amongst secondary school pupils in England, by social strata. We used linked records from state-funded schools and national health services (ECHILD) in England to create a secondary school cohort of 5,629,719 pupils entering Year 7 from 2012/13 to 2021/22. We measured rates of service use by gender, racial-ethnic group, free school meal (FSM) eligibility, the index of multiple deprivation (IMD) and region of residence. Service contacts were captured in the Mental Health Services Data Set and Hospital Episode Statistics. Pupils were followed up until the first chronological event of: service contact, age 21 years, death or end of study (31st August 2022). We found higher rates of mental health-related service use among females, adolescents who were FSM eligible, in the most deprived IMD groups, living in the North of England and from White Irish Traveller and Mixed Black Caribbean-White racial-ethnic groups. Consistently lower rates were estimated for males, adolescents living in London and Bangladeshi, Indian, Pakistani and Black African racial-ethnic groups. There was consistency in relative rates across services, particularly by FSM eligibility, IMD groups and racial-ethnic group. We present the first national estimates of referrals to mental health services, alongside hospital contacts, within a school cohort. We found stark variation in rates of contacts by social strata, which were broadly consistent across service types.